Dehydrated alfalfa pellets and soybean meal/grain sorghum in step-up winter supplementation programs for spring-calving beef cows - Vanzant, E.S.; Cochran, R.C.; Corah, L.R.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The performance response to a stepwise increase in the level of supplement fed to cows across the winter supplementation period was studied by feeding 112 Hereford × Angus cows the following treatments: dehydrated alfalfa pellets (DEHY) or soybean meal/grain sorghum (SS), each either level-fed (constant daily amount from December 1 to calving) or fed in a step-up program (low level from December 1 to 30; moderate level from December 31 to January 29; high level from January 30 to calving; avg = amount fed with level-feeding). Cow weight and condition changes and calf performance were favored by the step-up supplementation program when SS was fed. When DEHY was fed, cow weight and condition changes favored level-feeding. Weight and condition changes generally favored the DEHY group over the SS group. No effects were found for the reproductive characteristics measured. These results indicate that potential benefits of step-up winter supplementation programs depend on the type of supplement being fed. All of the supplementation programs appeared adequate to support desirable levels of reproductive performance.
Keywords: Beef; Beef cows; Protein supplement; Dehydrated alfalfa pellets; Winter range